2022
DOI: 10.1267/ahc.22-00043
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Mouse-on-mouse Immunohistochemical Detection of Mouse ESR2 Proteins with PPZ0506 Monoclonal Antibody

Abstract: Despite the physiological significance of ESR2, a lack of well-validated detection systems for ESR2 proteins has hindered progress in ESR2 research. Thus, recent identification of a specific anti-human ESR2 monoclonal antibody (PPZ0506) and its specific cross-reactivity against mouse and rat ESR2 proteins heightened momenta toward development of appropriate immunohistochemical detection systems for rodent ESR2 proteins. Building upon our previous optimization of ESR2 immunohistochemical detection in rats using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In parallel with our study, another research group has recently worked on the improvement of immunohistochemical detection protocols for ERβ in murine tissues [ 63 ]. The respective research group came up with a protocol that methodologically differs from our protocol in some steps, such as the use of HRP-polymer-bound secondary antibodies instead of the avidin-biotin detection system [ 63 ]. In line with our findings, the authors concluded that the monoclonal antibody PPZ0506 directed against amino acids 2–88 of human ERβ is a suitable mean to detect ERβ in murine tissues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In parallel with our study, another research group has recently worked on the improvement of immunohistochemical detection protocols for ERβ in murine tissues [ 63 ]. The respective research group came up with a protocol that methodologically differs from our protocol in some steps, such as the use of HRP-polymer-bound secondary antibodies instead of the avidin-biotin detection system [ 63 ]. In line with our findings, the authors concluded that the monoclonal antibody PPZ0506 directed against amino acids 2–88 of human ERβ is a suitable mean to detect ERβ in murine tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors present an additional step that can be applied to further reduce non-specific background effects. They show that one way to reduce endogenous Igs is to perfuse the living animals in deep anesthesia with saline buffer and fixative before tissue collection [ 63 ]. To perform such technique, an application requiring approval is a mandatory in the European Union according to Directive 2010/63/EU [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Single-cell RNA-seq and immunohistochemistry with a validated antibody have determined a highly restricted expression pattern with expression primarily in granulosa cells of the ovary ( Fig. 3A and 3B ) and in human testis ( 7 ), but not mouse testis ( 91 ). The few positive cells in human testis have later been identified as spermatids and spermatocytes through single-cell RNA-seq ( 87 ).…”
Section: Ovarian Estrogen Signalingmentioning
confidence: 99%